Leiomyoma in a Renal Allograft - Yan Jun Li; Amila Rohan Siriwardana; James Lawrence Penn Symons; Gordon Francis O’Neill; Min Ru Qiu; Timothy John Furlong (Case Reports in Urology)
Leiomyomas are smooth muscle tumours that are rarely found in the kidney. There is one report of a leiomyoma in a kidney transplant in a paediatric recipient. Here, we report an adult renal transplant recipient who developed an Epstein-Barr virus-positive leiomyoma in his allograft 15 years after transplantation. The patient was converted to everolimus for posttransplant immunosuppression management and there was no sign of progression over a year.